Anthracene‐thieno[3, 4‐c]pyrrole‐4, 6‐dione based donor–acceptor conjugated copolymers for applications in optoelectronic devices. (5th November 2015) - Cartwright, Luke; Neal, Thomas J.; Rutland, Nathan J.; Iraqi, Ahmed
Abstract : Three novel alternating copolymers of thieno[3, 4‐ c ]pyrrole‐4, 6‐dione (TPD) and triisopropylsilylacetylene‐functionalized anthracene were prepared via Suzuki polymerization. Various solubilizing substituents were attached to the TPD moiety in order to ascertain the impact they have upon the optical, electrochemical, and thermal properties of the resulting polymers. All copolymers showed good solubility and thermal stability with decomposition temperatures in excess of 300°C. Optical properties revealed that PTATPD(O), PTATPD(DMO), and PTATPD(BP) displayed optical energy gaps in excess of 2.0 eV. It is speculated that steric repulsion between solubilizing groups on repeat units along polymer chains reduces their planarity and decreases their electronic conjugation. The amorphous nature of the polymers was confirmed with differential scanning calorimetry and powder X‐ray diffraction. The highest occupied molecular orbital levels of the three polymers are unaffected by the different solubilizing chains. However, they exert some influence over the lowest unoccupied molecular orbital (LUMO) levels with PTATPD(BP) and PTATPD(O) displaying the lowest LUMO levels (−3.4 eV). In contrast, PTATPD(DMO) displayed the highest LUMO level (−3.3 eV). © 2015 The Authors. Polymers for Advanced Technologies Published by John Wiley & Sons Ltd.